2017
DOI: 10.3390/en10081153
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation for the Impact of Single Groove on the Stall Margin Improvement and the Unsteadiness of Tip Leakage Flow in a Counter-Rotating Axial Flow Compressor

Abstract: Abstract:A low-speed counter-rotating axial flow compressor (CRAC) with single circumferential grooved casing treatment (CT) was investigated numerically. Both steady and time-accurate numerical calculations were performed to study the effects of the single grooved CTs over the rear rotor on the stability enhancement and the unsteadiness of tip leakage flow (TLF) in the CRAC. Parametric studies indicate that the best position of the single groove should be located near about 20% axial tip chord in terms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Cevik et al [15] studied circumferential grooves with a saw tooth shape. Houghton and Day [16,17], Sakuma et al [18], and Mao et al [19] investigated the influence of the position and size of a single square groove on the compressor performance. Sakuma et al [18] found that a groove located at 0.2 axial chords from the leading edge of the blade was the best position for this design feature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cevik et al [15] studied circumferential grooves with a saw tooth shape. Houghton and Day [16,17], Sakuma et al [18], and Mao et al [19] investigated the influence of the position and size of a single square groove on the compressor performance. Sakuma et al [18] found that a groove located at 0.2 axial chords from the leading edge of the blade was the best position for this design feature.…”
Section: Introductionmentioning
confidence: 99%
“…Sakuma et al [18] found that a groove located at 0.2 axial chords from the leading edge of the blade was the best position for this design feature. Mao et al [19] numerically showed that the circumferential groove also improves the operating range of an advanced counter-rotating axial flow compressor.…”
Section: Introductionmentioning
confidence: 99%